Antioxidant Activity of Coumarine Compounds - Al-Majedy, Yasameen K; Ibraheem, Hiba H; Jassim, Liblab Sami; Al-Amiery, Ahmed A (Al-Nahrain Journal of Science, 2019)
Synthesis of coumarins, that were a structurally motivating antioxidant action, was finished in our article. Four components are condensed in the synthesis 4-hydroxycoumarin, 5,5-dimethyl-1,3-cyclohexanedione, and aromatic aldehydes, using tetrabutylammonium bromide (TBAB), diammonium hydrogen phosphate (DAHP), respectively to yield target compounds(1-4). The present methods have advantages, including one-pot synthesis, excellent yields, short reaction times, and easy isolation of product. All catalysts utilized in our study could be reused several times without losing their catalytic efficiency. The structures of the synthesized compounds were elucidating by spectro-scopically methods, Infrared Spectra FT-IR and 1H and 13C Nuclear/Magnetic/Resonance Spectra and elemental analysis techniques, melting point and thin layer chromatography. The scavenging activities of individual molecules were tested vs. stable free radical(1,1-Diphenyl-2-picrylhydrazyl (DPPH)), the results were compared to the Gallic acid. The results show that most of the compounds exhibited higher antioxidant activates than the standards in different concentration range. The highest efficiency scavenging activity was found for compound 2 (88.0±1%) followed by compounds 3 (83±0.5%).The component of the integrated mixes as cell reinforcements was likewise examined.